2005
DOI: 10.1002/aoc.891
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption characteristics of tributyltin on municipal solid waste compost

Abstract: The sorption behaviour of tributyltin (TBT) from reconstituted seawater onto municipal solid waste (MSW) compost was investigated to give first insights into the equilibrium and kinetic behaviour of this process. The rate of adsorption, the influence of pH, and the adsorbate hydrophobicity on the partitioning process were investigated. Adsorption kinetics indicated an initial fast rate of adsorption of TBT followed by a slower rate. The similarity of Freundlich sorption and desorption coefficients for TBT show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Adsorption is therefore an important process that can be used to reduce the concentration of TBT in harbors and/or in wastewaters before they are discharged into the marine environment. The adsorption of TBT onto sediments, clay (Hoch et al, 2002), mineral surfaces (Weidenhaupt et al, 1997), dead and live cells of microalgal species (Tam et al, 2002), municipal solid waste compost (Said-Pullicino and Vella, 2005) and iron oxides (Ottosen et al, 2005) has been reported; however, the use of oxides for the remediation of OTC usually resulted in between 56% and 76% OTC removal (Honda and Takahashi, 2006). Microbial remediation (Tam et al, 2002) also appears to be a possible removal method but only if the concentration of OTC is not too high.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption is therefore an important process that can be used to reduce the concentration of TBT in harbors and/or in wastewaters before they are discharged into the marine environment. The adsorption of TBT onto sediments, clay (Hoch et al, 2002), mineral surfaces (Weidenhaupt et al, 1997), dead and live cells of microalgal species (Tam et al, 2002), municipal solid waste compost (Said-Pullicino and Vella, 2005) and iron oxides (Ottosen et al, 2005) has been reported; however, the use of oxides for the remediation of OTC usually resulted in between 56% and 76% OTC removal (Honda and Takahashi, 2006). Microbial remediation (Tam et al, 2002) also appears to be a possible removal method but only if the concentration of OTC is not too high.…”
Section: Introductionmentioning
confidence: 99%
“…The dissolved organic matter in water sample leads also to incomplete derivatization and underestimation of the concentration of OTCs. [52][53][54] In this study the concentration of suspended solids was mainly below 20 mg L −1 except for 29th May 2012 and 5th June 2012 when the amounts were 95 mg L −1 and 220 mg L −1 , respectively. At that time untreated waste water was released to Lake Päijänne, due to malfunction at WWTP.…”
Section: Monitoring Of Otcs In Waste Water Grab Samplesmentioning
confidence: 50%
“…Filtering the samples did not reduce the OTC content dramatically which can be due to incomplete derivatization caused by suspended solids. [52][53][54] It also appeared that the concentrations in filtered and in unfiltered grab samples were generally higher than the ones detected in passive samplers. However, passive samplers concentrated OTCs for three days which allowed the enrichment of trace contents to measurable level.…”
Section: Resultsmentioning
confidence: 95%
“…Studies on the adsorption of BTs to different matrices have been widely reported. These matrices include clays (Hermosin et al 1993;Hoch et al 2003;Weidenhaupt et al 1997), quartz (Behra et al 2003;Bueno et al 1998), amorphous silica (Weidenhaupt et al 1997), metal oxides (Randall and Weber 1986;Weidenhaupt et al 1997), organic matters (Arnold et al 1998;O'Loughlin et al 2000;Said-Pullicino and Vella 2005), BCs (Brandli et al 2009;Fang et al 2010Fang et al , 2012, natural soils, and sediments (Burton et al 2004;Burton et al 2006;Huang and Matzner 2004). Studies have demonstrated respectively.…”
Section: Adsorption Of Btsmentioning
confidence: 99%